2019
DOI: 10.3390/su11143924
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Obesogenic Food Environments in South Africa and Ghana: Correlations and Contradictions

Abstract: In sub-Saharan Africa, urbanisation and food systems change contribute to rapid dietary transitions promoting obesity. It is unclear to what extent these changes are mediated by neighbourhood food environments or other factors. This paper correlates neighbourhood food provision with household consumption and poverty in Khayelitsha, South Africa and Ahodwo, Ghana. Georeferenced survey data of food consumption and provision were classified by obesity risk and protection. Outlets were mapped, and density and dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 97 publications
(151 reference statements)
7
45
0
Order By: Relevance
“…Food retail outlets and prepared food sources consisted mainly of open-air market sellers and food kiosks. This finding is similar to findings that have reported high presence of informal retail outlets in Uganda, Ghana, Zambia and South Africa [ 21 , 22 , 38 ]. The percentage of the supermarkets/minimart, retail outlets and fast-food restaurants were higher at the study sites in Nairobi compared to those in Kisumu, while open-air market vendors were predominant at the study sites in Kisumu.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Food retail outlets and prepared food sources consisted mainly of open-air market sellers and food kiosks. This finding is similar to findings that have reported high presence of informal retail outlets in Uganda, Ghana, Zambia and South Africa [ 21 , 22 , 38 ]. The percentage of the supermarkets/minimart, retail outlets and fast-food restaurants were higher at the study sites in Nairobi compared to those in Kisumu, while open-air market vendors were predominant at the study sites in Kisumu.…”
Section: Discussionsupporting
confidence: 91%
“…Studies have shown that availability of healthy food options vary across multiple factors including type of vendor and neighborhood socio-economic status amongst others. Formal retailers in Ghana were predominant sources of unhealthy foods including sugary drinks, confectioneries, sugar while in South Africa, formal retailers predominantly provided a mix of healthy and unhealthy food options like highly processed meats, sugar, legumes and vegetables [ 38 ]. Studies conducted in the United States have shown that grocery stores and supermarkets offer a larger variety healthy food options compared to corner stores and convenience stores [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…We designed questions on food source to capture how and where consumed foods were sourced and the extent to which those sources were utilised. The questions were centered on whether individuals source their food through their own production (growing, gathering, hunting or fishing), purchasing (from various retailers or food service business, as indicated in Table 1), borrowing/exchanging/bartering (BEB) or food aid; categories as recommended by the diet diversity framework [24] and research conducted in similar settings [25]. We obtained further details by asking standardised follow-up questions according to individual responses, aimed at determining the type of food sourced in given ways, and how frequently those foods were consumed.…”
Section: Food Sourcesmentioning
confidence: 99%
“…Step 4. Kroll et al (2019) found in urban Ghana that supermarkets were the largest source of sugary drinks (around 55%) with informal vendors also being a major source (around 38%) (Kroll et al, 2019). Bragg et al (2017) found that billboard advertising in Accra for sugary drinks was adult directed.…”
Section: Boxmentioning
confidence: 99%